Persistence and residues of oryzalin in soils under soybean crop - Blanco, Hélio Garcia; Oliveira, Domingos de Azevedo; Matallo, Marcus Barifouse (Pesquisa Agropecuaria Brasileira, 2014)
The persistence of oryzalin (3,5-dinitro-N-N-dipropylsulphanilamide) under field conditions was investigated for three consecutive years in three soils cultivated with soybean (Glycine max (L.) Merrill). The presence of this herbicide was assessed by sorghum bioassay conducted under phytotron conditions. Oryzalin at 1.50 to 2.25 kg/ha persisted in the top soil (0 cm - 10 cm depth) at 15 weeks after treatment. Oryzalin was not present at phytotoxic levels in soil samples taken from treated plots at 20 weeks after treatment. Oryzalin residues below 0.180 ppm determined by gas chromatography showed no herbicidal activity on the test plants.